Impact evaluation report of Egypt’s Forsa Graduation Program - Allen IV, James; Gilligan, Daniel O.; Kurdi, Sikandra; Shokry, Nada; Yassa, Basma (International Food Policy Research Institute, 2023)
1. Forsa, which means “Opportunity” in Arabic, is a new economic inclusion program of the government of the Arab Republic of Egypt. Implemented by the Ministry of Social Solidarity (MoSS), one major goal of the program is to graduate beneficiaries of Takaful to economic self reliance by enabling them to engage in wage employment or small-scale productive enterprises. 2. The Forsa program began in 2023, after significant delays. Obstacles to implementation in cluded the Covid-19 pandemic, nationwide inflation subsequent to the Ukraine-Russia war result ing in funding challenges for asset purchases, and administrative challenges with procurement approvals by the Ministry of Finance. Forsa implementation was conducted under MoSS super vision by local non-governmental organizations (NGOs). While a few NGOs received their first payments in the first quarter of 2022, most NGOs received their first payments in October 2022, delaying program implementation to February 2023. According to the MoSS, in the second half of 2023, households receiving assets through the program increased from around 3,000 (9%) to 10,302 (29%) out of a target of 35,000 households through 49 contracted NGOs and two private hiring firms, and the number of participants receiving a job has increased from 3,324 (23%) in August to 5,392 (38%) by end of November of 2023 out of a target of 14,314 households through 22 NGOs and two private firms.